How does social capital shape the response to environmental disturbances at the local level? Evidence from case studies in Mexico - Cohen-Salgado, D.; García-Frapolli, E.; Mora, F.; Crick, F.
Even though there is an increasing recognition of the importance of supporting local level adaptation to disasters associated to climate change, it is still not fully understood how communities cope with them. In particular, a key dimension that is less well understood is the importance of social capital and the role it plays in enabling communities to respond. This research aims to address this gap through a case study with two semi-coastal communities in Mexico that have being hit by hurricanes recently. Structured and semi-structured interviews were carried out to collect data, which was analyzed through an interpretive approach. Network analysis was also carried out to explain the role of the different actors in the response to disturbances as hurricanes and the possible relationship with social capital. Results showed that social capital is relevant for coping with hurricanes; although bonding relationships were acknowledged as the most relevant for supporting when these events occur; linking relationships were also recognized as fundamental, particularly for responses on the long term (productive diversification, improvements in infrastructure). These findings are useful for designing better-fitted schemes towards adaptation, as one of the communities showed more vulnerability due to an absence of links with external actors. Also, it demonstrates that climate change research with different approaches, such as network analysis, is fundamental to get more in-depth data to design context specific strategies to cope with disasters associated to this phenomenon.
Keywords: DISASTERS; HURRICANES; NETWORK ANALYSIS; SOCIAL CAPITAL; ADAPTATION